HBR Guide to : Women at Work - Harvard Business Review (Harvard Business Review Press, 2019)
The HBR Guide for Women at Work will help you identify and overcome the factors that are holding you back. It provides practical tips and advice so you can face gender stereotypes head-on, make yourself visible when opportunities arise, and demonstrate your leadership skills.You'll learn to : Speak up in meetings in a way that ensures your ideas will be heard. Wield influence by building the right relationships. Advocate for yourself--and for what you want. Align yourself with mentors and sponsors to support your growth. Show passion without being perceived as "too emotional".Create your unique vision as a leader